Exploring the Development of Communication Abilities of Intermediate-High Spanish Learners during Online Chatting - D’Amico, Melanie (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This project explores how intermediate-high learners of Spanish communicate during a real-world style chatting conversation. Further, this study investigates these learners’ ability to improve their communication over time as they are moving away from the effort of learning their L2 and toward the effort of applying that knowledge as they use the L2. To explore the use and development of communication abilities, online conversations (chats) were used due to their reduced-pressure contexts (Sun, 2007). Participants were 32 intermediate-high Spanish learners from an advanced grammar course. Learners completed five open topic online chatting sessions. These chats were analyzed for the use of twelve communication tactics: openings, closings, pre-closing devices, direct requests, indirect requests, mitigated speech, circumlocution, follow-up questions, message abandonment, code switching, self-correction, and other-correction. Results found a significant increase in closings and follow-up questions along with a significant decrease in code switching from Chat 1 to Chat 3. Following Chat 3, these significant changes were maintained in Chats 4 and 5 (despite a slight increase in code switching during Chat 5). Additionally, from Chat 1 to Chat 4, significant increases were seen in circumlocution and self-correction and from Chat 1 to Chat 5, a significant decrease was seen for topic abandonment. These results show positive development over time to higher quality conversations with a desire to better maintain and explore topics. Further, learners attempted to remain in Spanish using less code switching and greater circumlocution to convey their meaning. At the same time, learners worked toward greater accuracy through their increased self-corrections.